Mass Ratio Influence on Vortex-Induced Vibration of a Flexible Cylinder using Large Eddy Simulation at Re=1000 - An-Nizhami, Avicenna; Apriandi, Nanang; Setiawan, Trio; Kristiawan, Timotius Anggit; Riadini, Elfrida Rizky; Janitra, Atikah Ayu; Yanuar, Padang (Journal of Mechanical Engineering and Applied Technology, 2024)
The study investigates the phenomenon of vortex-induced vibration (VIV) using Large Eddy Simulation (LES) at a Reynolds number of 1000, focusing on transitional flow conditions. LES has proven effective in understanding VIV across Reynolds number regimes, aiding in comprehending flow physics and mechanisms behind VIV. The research aims to contribute data for validating numerical models and informing engineering practices. The study employs the Navier-Stokes equation and the continuity equation to analyze fluid flow, treating it as incompressible due to negligible density changes. The three-dimensional incompressible momentum equation is discretized using the finite volume method within the spatial domain. Resolution of the pressure Poisson equation ensures compliance with free divergence conditions, enhancing computational fluid dynamics simulations' reliability. Validation of the fluid flow solver involves comparing computed drag force coefficients with established benchmarks, showing agreement within small discrepancies. The study delves into vibration behavior induced by cross flow at various reduced velocities (), noting distinct patterns ranging from irregularities at low  to quasi-periodic behavior at higher values. Analysis of maximum cylinder displacement () across different reduced velocities and mass ratios underscores the complex relationship between system parameters and displacement dynamics. A consistent occurrence of y_max at a specific reduced velocity highlights its significance, while varying mass ratios affect displacement patterns, indicating the importance of understanding these dynamics for optimizing fluid-structure interaction systems.